Tinjauan Hukum Islam terhadap Jual Beli Buah Durian pada Pohonnya - Imam Mugi; Zaini Abdul Malik; Panji Adam Agus Putra (Bandung Conference Series: Sharia Economic Law, 2024)
Abstract. Buying and selling is an agreement to exchange objects (goods) that have value, on the basis of willingness (agreement) between two parties in accordance with the agreement or conditions justified by syara'. The practice of buying and selling contains elements of ghoror (obscurity). This violates the principles of Islamic law against buying and selling, where in Islamic law the practice of buying and selling one of the conditions must be clear. The reason for conducting this research is to find out how Islamic law reviews the practice of buying and selling durian on trees in the area of ​​Kampung Bojong Serang, Banten. This research belongs to the type of qualitative research, which is a process based on a methodology that investigates a social phenomenon and human problems. This sale and purchase is said to be permissible or permissible if both parties know the terms and pillars of the legal sale and purchase, but it is said to be invalid if the sale and purchase of durian fruit is seen from Islamic law the pillars have been fulfilled while the terms are not fulfilled because the object is not clear the quality and the quantity. Abstrak. Jual beli adalah suatu perjanjian tukar menukar benda (barang) yang mempunyai nilai, atas dasar kerelaan (kesepakatan) antara dua belah pihak sesuai dengan perjanjian atau ketentuan yang dibenarkan oleh syara’. Praktik jual beli itu terdapat unsur ghoror (ketidak jelasan) hal ini melanggar perinsip hukum Islam terhadap jual beli, dimana dalam hukum islam praktik jual beli salah satu syaratnya harus jelas. Alasan melakukan penelitian ini adalah untuk mengetahui bagaimana tinjauan hukum Islam terhadao praktik jual beli durian di pohon di daerah Kampung Bojong Serang Banten. Penelitian ini termasuk kedalam jenis penelitian kualitatif, yaitu suatu proses berdasarkan pada metodologi yang menyelidiki suatu fenomena sosial dan masalah manusia. Jual beli ini di katakan mubah atau boleh dilakukan apabila kedua belah pihak mengetahui syarat dan rukun sahnya jual beli, namun dikatakan tidak sah apabila jual beli buah durian dipohon di lihat dari hukum islam sudah terpenuhi rukunnya sementara secara syarat tidak terpenuhi karena objeknya tidak jelas kualitas dan kuantitasnya.